Loi et héritage culturel - Sparer, Michel; Schwab, Wallace (Les Cahiers de droit, 1979)
Is legal drafting to be considered an autonomous discipline or should it be relegated to a set of grammatical rules ? Or yet still, might it be elevated to a full-fledged area of legal studies ? The scope of the matter goes far beyond simple considerations of numbering paragraphs, punctuation, and uses of language. Interest for legal drafting in Québec is the result of a relative imbalance between information on the subject in French and in English. At a time when legislative texts extend their authority to all strata of the population, it is essential that these texts be understandable and accessible. When discussing legal drafting, there is a popular distinction that is inevitably made between the form and the substance of the law. This idea, while sometimes valid, constitutes a gross oversimplification of reality, for where does form end and substance begin or vice versa ? Nor is it found that this traditional distinction settles the sticky question of structure in the law. The establishment of rules for drafting in French can not and must not proceed from a literal translation of English rules or practices, for the thought processes of these languages are far too different. For this reason, it has been necessary to undertake a meticulous empirical approach to describe just what characterizes the French use of legal language. Generally speaking, in French, the law should be an abstract declaration of principles ; specifics of application are left either to regulations or to judiciary construction. As the major vehicle for transmitting social standards, the law must be straightforward in maintaining an equitable continuity in social practices and institutions. This suggests that the law must be clear and unequivocal, yet how is one to define clarity; admittedly here is an embarrassing concept. It seems preferable to attack the problem by eliminating ambiguity, i.e. to reduce those legal, stylistic, structural or lexical elements which hamper comprehension. Laws can be written understandably, but do they still reflect the cultural needs of their intended audience ? The question remains largely unanswered. Is parliamentary procedure the best way to produce a body of legislation ? When one considers the diverse training of members of parliament and the urgency of their work, is it no wonder that laws often leave much to be desired... The composition of laws involves numerous details of which only the main ones are discussed here ; preamble, title, sub-titles, definitions, purpose, powers, obligations, responsible body, enabling provisions, coming into force, marginal notes. Discussing these matters brings to light various factors such as: 1. the frequent gap between the content of the preamble and the substance of the law; 2. the information contained in the title with respect to the substance of the law; 3. the abuse of definitions wherein one finds the substance of the law, unusual use of words, confusion, enumerations and a paralysing effect on the evolution of the law; 4. the necessity for underscoring powers, obligations as well as the purpose of legislation. Such considerations lead inevitably to a reassessment of what codifying the law is all about, a means for managing large volumes of textual material, for updating obsolescent and amputating dead provisions. Codification means that all possible structures of legislation must be understood; in civil law particularly, this implies deductive reasoning which proceeds from the general to the specific. Jmplicity takes priority over expliciteness and principles of « ejusdem generis » and « expressio unius, exclusio alterius » are of marginal value. The physical make-up of a code must take into account such factors as: 1. the dimension of its articles, i.e. one idea or concept per article; 2. the limited use of verb tenses, i.e. usually the present tense; 3. the use of the active voice; 4. the precise use of negations; 5. the elimination of redundancies; 6. the use of clear syntactic structures, i.e. subject + verb + complement ; 7. the correct use of French pronouns; 8. the abuse of demonstrative adjectives; 9. the correct use of references. Following these considerations, it becomes tempting to reason in terms of model or stereotyped legislation wherein only one form should prevail ; however, although organized to standards, legislation must remain dynamic to be effective. Finally, the cultural basis of drafting legal material must remain everpre-sent in the minds of draftsmen, for there are elementary, but pervasive elements of English and French thinking which will always come into play and orient the writer. For instance, the French will inevitably qualify something generally, where the English will prefer describing concretely the same phenomenon. Hopefully, by refining techniques of drafting, the often exagerated need for rules of interpretation will diminish and the law will stand as it should, on its own merits.